Long-Term Biocompatibility of a Highly Viscously Thiol-Modified Cross-Linked Hyaluronate as a Novel Vitreous Body Substitute - Hurst, Jose; Rickmann, Annekatrin; Heider, Nele; Hohenadl, Christine; Reither, Charlotte; Schatz, Andreas; Schnichels, Sven; Januschowski, Kai; Spitzer, Martin S. (Frontiers in Pharmacology, 2022)
Purpose: In surgical ophthalmology, the treatment of complicated retinal and vitreous diseases is one of the central challenges. For this purpose, the vitreous body is removed as part of the standard therapy and replaced by a temporary tamponade to stabilise the position of the retina. Since the tamponading properties of previous materials such as silicone oils, gases or semi-fluorinated alkanes are a combination of their surface tension and their buoyancy vector, they cannot completely fill the vitreous cavity. The aim of this work was to test in vivo a novel vitreous body substitute (Vibos strong) based on cross-linked hyaluronic acid for its compatibility. Methods: A pars plana vitrectomy with posterior vitreous detachment was performed in the right eye of 18 pigmented rabbits, with subsequent injection of ViBos strong. Follow-up examination included slit lamp examination, funduscopy, intraocular pressure measurements (IOP), optical coherence tomography (OCT) and electroretinogram (ERG) measurements. The rabbits were sacrificed at three different time-points (1, 3 and 6 months; each 6 animals) and examined macroscopically and prepared for histological examination (HE staining) and immunohistochemistry (Brn3a and GFAP). Results: ViBos strong demonstrated good intraoperative handling and remained stable for at least one month and degraded slowly over six months. IOP was within clinical acceptable values at all follow-up examinations. Retinal function was well preserved after instillation of the hydrogel and comparable to the untreated eye after six months in OCT, ERG and histological examinations. An increase in the GFAP expression was found in the surgery eyes, with a peak in the 3 months group. The Brn3a expression was not significantly affected by vitrectomy with ViBos strong. Conclusions: Highly viscously thiol-modified crosslinked hyaluronate showed a good biocompatibility in rabbit eyes over 6 months after vitrectomy making it a promising potential as a vitreous substitute.